Os signos e símbolos na construção de conceitos por meio das instalações geográficas - Silva, Alexandre Ribeiro da (2024)
The research developed in this thesis aims to understand the role of signs and symbols in the construction of concepts through Geographic Installations. To this end, we conducted a bibliographic research using photographic records captured during the exhibition phase of Geographic Installations, in their particular contexts, involving social groups and addressing different themes. We believe that photography represents a powerful tool for the documentation of timeless images, capable of preserving the interests, ideologies, creativity, and underlying concepts proposed in a given context. The semiotic elements present in Geographic Installations, such as objects, colors, shapes, and spatial arrangements, are essential for the communication of complex messages in an intuitive and implicit manner. The analyses we conducted were built with photographic images of Geographic Installations, which were obtained from reliable academic sources, specifically taken from the dissertations of Silva (2019), Lobô (2022), and Alencar (2020), available in the Dissertation and Thesis Bank of the Coordination for the Improvement of Higher Education Personnel (CAPES). Throughout our investigation, we focused on building a novel theoretical framework to explore the theories of signs and symbols for the contribution of geographic concepts within the scope of geography education. Learning is promoted by the development of thought and language, following the stages and phases outlined by Vygotsky, as demonstrated in our study. With this, we assert that the effectiveness of the Geographic Installation methodology stands out, particularly with students in Upper Elementary and High School. We conclude that Geographic Installations, by incorporating varied semiotic elements, facilitate the representation and materialization of geographic concepts such as places, landscapes, regions, territories, and the scale of phenomena. Therefore, Geographic Installations offer a valuable opportunity to explore and understand these concepts in a visual and artistic context.